Linie i strefy różnic odległości z siedlisk do działek i ich oddziaływanie na przebieg granic między ospodarstwami - Harasimowicz, S.; Janus, J. (Видавництво Національного університету "Львівська політехніка", 2007)
Distance between farmlands and household dwellings present one of the most important factors that have a bearing on profitability of agricultural production. Presented editorial contains a description of methodology of determining lines and zones of equal variances of distances from farm holdings to land plots within the area of Filipowice village. The analysis was conducted based on calculated matrix of distances of all farm holdings to all land plots situated in the given village, counted along agricultural transport routes. The presented methodology may represent an element of valuation of agricultural land spatial structure. A matrix used in calculation represents also an important element of optimizing procedures for agricultural land arrangement.